Association between HIV infection and outcomes of care among medicare enrollees with breast cancer - Chhatre, Sumedha (EClinicalMedicine, 2019)
BACKGROUND: To assess the interaction of breast cancer, HIV infection, Medicare disability status, cancer stage and its implications for outcomes, after accounting for competing risks among female, fee-for-service Medicare enrollees. METHODS: We used data from Surveillance, Epidemiology and End Results (SEER) -Medicare (2000–2013). From primary female breast cancer cases diagnosed between 2001 and 2011, we identified those with HIV infection. We used Generalized Linear Model for phase-specific incremental cost of HIV, Cox regression for association between HIV and all-cause mortality, and Fine and Gray competing risk models to assess hazard of breast cancer-specific mortality by HIV status. We also studied this association for subgroups of cancer stage and disability status. FINDINGS: Of 164,080 eligible cases of breast cancer, 176 had HIV infection. Compared to HIV-uninfected patients, HIV infected patients had 16% higher cost in initial phase, and 80% higher cost in interim stage of care, and at least two times higher mortality (all-cause and breast cancer-specific), after accounting for competing risk. Among disabled enrollees, HIV-infected patients had higher risk of all-cause and breast cancer-specific mortality, compared to HIV-uninfected patients. INTERPRETATION: Female fee-for-service Medicare enrollees with breast cancer experience higher initial and interim phase cost and worse survival in the presence of HIV. This association was also significant among disabled Medicare enrollees. Medicare is the single largest source of federal financing for HIV care. Burden on Medicare will grow exponentially due to higher proportion of disabled among HIV-infected enrollees, longer survival among HIV- infected persons, increased HIV incidence in older adults, and increased age related risk of breast cancer. Future research can identify the pathways via which HIV infection affects cost and mortality, and develop integrated strategies for effective management of concomitant breast cancer and HIV and inform survivorship guidelines. FUNDING: National Institute on Aging, National Institutes of Health, Grant # R21AG34870-1A1